1989
DOI: 10.1177/000331978904000603
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Ultrasound for Diagnosis of Symptomatic Venous Thrombosis and for Screening of Patients at Risk: Correlation with Ascending Conventional Venography

Abstract: This is a prospective study of 108 patients in two distinct groups undergoing real-time ultrasonography (US) and ascending conventional venography within the same day. The two patient groups consisted of the following: Those patients evaluated because of suspicion of deep venous thrombosis of lower limbs (69 patients) and those at high risk for venous thrombosis (19 patients with a recent hip fracture, 20 with a suspected pulmonary embolism). In the diagnosis group 48 patients had venographic evidence of throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Real-time Bmode ultrasound scanning was performed using a com mercially available scanner with a 7.5-MHz sector imaging transducer, as previously reported elsewhere [16]. PE was considered in patients with clinical symp toms, high-probability defects on ventilation-perfusion lung scan, and documentation of venous thrombosis of the lower extremities.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Real-time Bmode ultrasound scanning was performed using a com mercially available scanner with a 7.5-MHz sector imaging transducer, as previously reported elsewhere [16]. PE was considered in patients with clinical symp toms, high-probability defects on ventilation-perfusion lung scan, and documentation of venous thrombosis of the lower extremities.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…9, [46][47][48][49] Numerous investigators have confirmed that CUS is nearly 100% sensitive and specific for the diagnosis of proximal DVT. 47,[49][50][51][52] Although CUS fails to adequately identify calf thrombi (<50 % sensitivity) 49,53,54 , only 20% to 30% of calf thrombi extend proximally and these are rarely asymptomatic. 12 Follow-up studies performed 7 days after an initially negative CUS have identified only 1% 51 to 1.4% 52 of patients with the subsequent development of DVT.…”
Section: I a G N O S T I C M O D A L I T I E Smentioning
confidence: 99%
“…Sensitivity ranges from 89% to 100% while specificity ranges from 86% to 100%. 2,8,14,21,24,27 Other methods of examining accuracy of compression ultrasound for DVT have been examined. Two large prospective trials have investigated this question using follow up ultrasound examinations.…”
Section: Duplex Ultrasound Evaluation Of Symptomatic Acute Dvtmentioning
confidence: 99%